Tax on interest and the pricing of personal demand deposits - Juha Tarkka (Bank of Finland, 1992)
The paper analyzes the effects of taxation on the pricing of personai transactions deposits such as chequing accounts. In many fiscal systems, explicit interest on deposits is taxable while "implicit interest" in the form of underpriced bank services for depositors is not. Conditions are developed under which this asymmetry leads to zero deposit rates, zero service charges, ar both. Minimum balance requirements are also explained. It is found that the asymmetric tax system generally involves an implicit subsidy to the service production activities of banks. The subsidy to banking is increases when the tax rate on interest income is increased. The analysis is extended to the Finnish system of tax exempt regulated deposit rates. The implicit subsidy to the real activities of banks is shown to be even larger in this system.
URN:NBN:fi:bof-201808021849
Keywords: 330